Overhead crane anti-swing system based on the Pontryagin’s maximum principle - Spruogis, Bronislovas; Jakštas, Arūnas; Gičan, Vladimir; Turla, Vytautas (Transport, 2015)
Overhead cranes are widely used at industrial enterprises for transportation of materials and products. They are successfully adaptable to technological processes used at an enterprise and their exploitation is inexpensive; in addition, the price of cranes is relatively low. However, extension of requirements set for technological processes results in shortened time for transportation and stiffened requirements for accuracy of cargo delivery and cargo safety. In the attempts to satisfy the latter requirements, particular attention is paid to swings of the cargo-holding rope. There is a number of factors that cause increased requirements for the control system of the crane drive. The slewing movement affects the total system of the crane and aggravates the crane movement control. In modern overhead cranes, the abilities and qualification of an operator (who is assisted by a certain anti-swing system) predetermine the cargo swings and the accuracy of its positioning. The said circumstance latterly caused a particular attention to computerisation of overhead crane control. However, a nonlinearity of the mechanical system of a crane and complicated control of swings often cause undesirable swings, in particular in the beginning and the end of cargo transporting process, thus reducing the efficiency of usual crane control systems. In addition, it should be taken into account that the parameters of a crane, as a controlled mechanical system, depend on the cargo and the conditions of its transportation. Consequently, a development of an effective cargo swing reduction system is a currently topical engineering problem. First Published Online: 27 Mar 2015